2018
DOI: 10.1002/clen.201800157
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Operational Parameters on the Iron(III) Uptake by Micro‐Algae Dunaliella salina

Abstract: The uptake of Fe(III) by living cells of unicellular green algae Dunaliella salina ions is investigated. The effects of operational conditions such as contact time, biomass concentration, initial pH, and initial Fe(III) concentration on iron uptake are studied. The time profile of the Fe(III) uptake by living cells of D. salina shows a time lag in the first 15 min, which is associated with the production of metal chelating agents. In addition, it is found that the optimum pH for maximal iron uptake is 8. At op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Thus, the present results are consistent with our earlier observations on intracellular and extracellular accumulation of metals in both the strains, MAS1 and MAS3, from synthetic AMD samples within a shorter incubation time . Such an enhanced removal at a higher cell density could be attributed to the increased sorption process as reported with Dunaliella salina in the removal of Fe . However, there was no significant difference in Fe removal by both the strains with a higher cell density even after 48 h incubation.…”
Section: Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the present results are consistent with our earlier observations on intracellular and extracellular accumulation of metals in both the strains, MAS1 and MAS3, from synthetic AMD samples within a shorter incubation time . Such an enhanced removal at a higher cell density could be attributed to the increased sorption process as reported with Dunaliella salina in the removal of Fe . However, there was no significant difference in Fe removal by both the strains with a higher cell density even after 48 h incubation.…”
Section: Results and Discussionsupporting
confidence: 93%
“…Moreover, immobilized cells of strains MAS1 and MAS3 exhibited changes in the region of 3000–3500 cm –1 , which could be attributed to the vibrations of OH and NH groups present on the cell surface. Anghel et al also observed strong absorption peaks at 3200, 3500, 1648, 1545, and 925–1150 cm –1 that correspond to OH and NH vibration stretching, primary and secondary amides in Fe-exposed cells of D. salina.…”
Section: Results and Discussionmentioning
confidence: 92%
“…Successful growths of several species of microalgae including Chlamydomonas sp., Euglena sp., Micractinium sp., Botryococcus sp., Coelastrum sp., Chlorella sp., Selenastrum sp., Scenesdesmus sp., Oscillatoria sp., and Microcystis sp., in different wastewater sources have been reported in detail. [ 9,16,21–24 ] Among all of them, Chlorella and Scenedesmus spp. are the most robust and versatile candidates due to their strong tolerance to different wastewater conditions ( Table 3 ).…”
Section: Microalgal Species For Wastewater Treatmentmentioning
confidence: 99%
“…Numerous studies have been reported on successful cultures of several species of microalgae such as Dunaliella salina‏ , Spirulina sp., Chlorella sp., Scenedesmus sp., Oscillatoria sp., Euglena sp., etc., in different wastewater, [ 16–19 ] but less frequently on diatoms as wastewater purifiers. [ 5,4,20–22 ]…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been reported on successful cultures of several species of microalgae such as Dunaliella salina , Spirulina sp., Chlorella sp., Scenedesmus sp., Oscillatoria sp., Euglena sp., etc., in different wastewater, [16][17][18][19] but less frequently on diatoms as wastewater purifiers. [5,4,[20][21][22] This study fits in the field of biotechnology and sustainable development, recyclable and recoverable biomaterials, and protection of receptor natural environments.…”
Section: Introductionmentioning
confidence: 99%